Methods of quality assurance for productionalization of cloud systems - Tasanen, Joona (2022)
In this study beneficial methods and instruments of quality assurance for productionalization of cloud systems were researched from the literature and from the case study done in the target organization. This case study was ordered by the target organization to help with quality assurance of cloud systems during productionalization. As implementing emerging technologies to new cloud systems provide increasing challenges to maintain high quality cloud services. From the results of the literary review and the case study 27 methods and instruments of quality assurance were found. There were several beneficial methods, including problem determination with automation and benchmarking. These methods will provide practical help for quality assuring cloud systems in the target organization. To extend the research in the field these results could be tested, and more case studies done in different organizations.